2019
DOI: 10.1097/md.0000000000014407
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of clinical outcomes and radiotherapy-associated toxicity in multicatheter accelerated partial breast irradiation

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Few systematic reviews and meta-analyses were conducted to compare the effectiveness of distinct PBI approaches with WBI for the treatment of patients with breast cancer [39][40][41][42] , showing that the balance between benefit and risk of PBI appears optimal for low-risk women 43,44 . Several phase 3 trials on external beam PBI versus WBI showed non inferior local control and comparable rates of distant metastases, breast cancer specific and overall survival in selected patients at low risk of recurrence [45][46][47] .…”
Section: Statement 4 Low Risk-features Suitable For Partial Breast Ir...mentioning
confidence: 99%
“…Few systematic reviews and meta-analyses were conducted to compare the effectiveness of distinct PBI approaches with WBI for the treatment of patients with breast cancer [39][40][41][42] , showing that the balance between benefit and risk of PBI appears optimal for low-risk women 43,44 . Several phase 3 trials on external beam PBI versus WBI showed non inferior local control and comparable rates of distant metastases, breast cancer specific and overall survival in selected patients at low risk of recurrence [45][46][47] .…”
Section: Statement 4 Low Risk-features Suitable For Partial Breast Ir...mentioning
confidence: 99%
“…2 Acute injury occurs during or a few months after radiotherapy and is usually self-limiting, including haematoma, dermatitis, breast pain and implant infection. 3 Late injury is that persisting at six months or occurring over six months after radiotherapy, and usually worsens with time. 4 The most common LRTI symptoms after breast cancer are pain, oedema, fibrosis, and limited range of motion of the arm at the shoulder joint.…”
Section: Introductionmentioning
confidence: 99%
“…Partial breast irradiation can be administrated through various techniques, including external beam RT, intra‐operative RT and brachytherapy [ 103 , 104 , 105 , 106 ]. Studies comparing the effectiveness of different APBI approaches with whole breast irradiation showed that low‐risk patients appear to be the optimal population for APBI treatment, considering the balance between benefit and risk [ 107 , 108 , 109 , 110 , 111 ]. More and long‐term results of several past and ongoing prospective randomized APBI trials are awaited.…”
Section: Early Breast Cancer: Local‐regional Treatmentmentioning
confidence: 99%